Faktor yang Mempengaruhi Pelanggaran Disiplin Siswa dan Implikasinya terhadap Layanan Bimbingan & Konseling - Ilahi, Ridho; Syahniar, Syahniar; Ibrahim, Indra (Universitas Negeri Padang, 2013)
Abstract Students’ discipline violation at SMA N X Padang are affected by internal and external factors. Findings in the field showed that many students broke the school’s discipline. This research is aimed to describe internal and external factors that affected students’ discipline violation and those implications for Counseling and Guidance services. This research is classified into quantitative research in descriptive type. The research subjects are 130 students who violate the discipline at SMA N X Padang. The research instrument is questionnaire. The findings of the research revealed: factors internal (psychology conditions) and external (school’s environment, family, and community).Keyword: Discipline violation